MicroRNA Analysis in Meningiomas with Different Degrees of Tissue Stiffness: A Potential Tool for Effective Preoperative Planning - Duba, Milos; Al Tukmachi, Dagmar; Samoilenko, Tetiana; Vecera, Marek; Ruckova, Michaela; Vankova, Tereza; Radova, Lenka; Kerkovsky, Milos; Dostal, Marek; Koprivova, Tereza; Roskova, Ivana; Mrlian, Andrej; et al. (Neurosurgery, 2024)
BACKGROUND AND OBJECTIVES: Meningioma, the most common primary intracranial tumor, presents challenges in surgical treatment because of varying tissue stiffness. This study explores the molecular background of meningioma stiffness, a critical factor in surgical planning and prognosis, focusing on the utility of microRNAs (miRNAs) as diagnostic biomarkers of tissue stiffness. METHODS: Patients with meningiomas treated surgically at the University Hospital Brno were included in this study. Total RNA, isolated from tumor tissue samples, underwent quality control and small RNA sequencing to analyze miRNA expression. Differentially expressed miRNAs were identified, and their association with tumor stiffness was assessed. RESULTS: This study identified specific miRNAs differentially expressed in meningiomas with different stiffness levels. Key miRNAs, such as miR-31-5p and miR-34b-5p, showed significant upregulation in stiffer meningiomas. These findings were validated using reverse transcription-quantitative polymerase chain reaction, revealing a potential link between miRNA expression and tumor consistency. The expression of miR-31-5p was most notably associated with the stiffness of the tumor tissue (sensitivity = 71% and specificity = 83%). CONCLUSION: This research highlights the potential of miRNAs as biomarkers for determining meningioma tissue stiffness. Identifying specific miRNAs associated with tumor consistency could improve preoperative planning and patient prognosis. These findings pave the way for further exploration of miRNAs in the clinical assessment of meningiomas.